2020
DOI: 10.1039/d0tc00840k
|View full text |Cite
|
Sign up to set email alerts
|

A novel precursor towards buffer layer materials: the first solution based CVD of zinc oxysulfide

Abstract: We report the first solution based deposition of zinc oxysulfide, Zn(O,S), thin films via aerosol-assisted chemical vapour deposition (AACVD) facilitated by the use of a specifically designed precursor: [Zn 8 (SOCCH 3 ) 12 S 2 ] (1). This buffer layer material, synthesised from the dual source AACVD reaction of 1 with ZnEt 2 and MeOH was analysed via X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), energy dispersive X-ray (EDX) analysis, scanning electron microscopy (SEM), Hall effect measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The Zn 2p 3/2 and 2p 1/2 states appeared at 1044.2 and 1021.2 eV respectively and one S environment was present, with 2p 3/2 and 2p 1/2 states appearing at 162.8 and 161.5 eV respectively, in accordance to previous reports from the literature for Zn(O,S) films. 26 One oxygen environment appeared at 529.5 eV for the 1s state, whilst a hydroxide state also appeared at 531.1 eV. There was however a change in binding energies for the surface scan as compared to the 300 s etch.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The Zn 2p 3/2 and 2p 1/2 states appeared at 1044.2 and 1021.2 eV respectively and one S environment was present, with 2p 3/2 and 2p 1/2 states appearing at 162.8 and 161.5 eV respectively, in accordance to previous reports from the literature for Zn(O,S) films. 26 One oxygen environment appeared at 529.5 eV for the 1s state, whilst a hydroxide state also appeared at 531.1 eV. There was however a change in binding energies for the surface scan as compared to the 300 s etch.…”
Section: Resultsmentioning
confidence: 94%
“…From elemental ratios, it was found that the S/Zn ratio on the surface was 1.73, indicating a sulfur rich environment as evidenced by absence of an oxygen environment, as well as a shift towards higher binding energies, whilst the S/Zn ratio for the bulk material (300 s etch) was calculated to be 0.40, in line with observed results. Previous work has shown that for zinc oxysulfide films produced via AACVD which have a S/Zn ratio above 0.13, 26 Hall effect data cannot be acquired due to the high resistivities of the films. The as-deposited films presented here have a high S/Zn ratio on the surface, therefore electronic data could not be acquired for film C .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations